Astrocytic Ryk signaling coordinates scarring and wound healing after spinal cord injury - Zhe Shen; Bo Feng; Wei Ling Lim; Timothy Woo; Yanlin Liu; Silvia Vicenzi; Jingyi Wang; Brian K. Kwon; Yimin Zou (Proceedings of the National Academy of Sciences, 2025)
Wound healing after spinal cord injury involves highly coordinated interactions among multiple cell types, which are poorly understood. Astrocytes play a central role in creating a border against the non-neural lesion core. To do so, astrocytes undergo dramatic morphological changes by first thickening and elongating their processes and then overlapping them to form a physical barrier. We show here that the expression of a cell-surface receptor, Ryk, is induced in astrocytes after injury in both rodent and human spinal cords. Astrocyte-specific knockout of Ryk dramatically elongated the reactive astrocytes, accelerated the formation of the border, and reduced the size of the scar. Astrocyte-specific knockout of Ryk also accelerated the injury responses of multiple cell types. Single-cell transcriptomics analyses revealed a broad range of changes in cell signaling among astrocytes, microglia, fibroblasts, and endothelial cells after astrocyte-specific Ryk knockout, suggesting that Ryk not only regulates injury responses of astrocytes but may also regulate signals emanating from astrocytes and coordinate the responses of these cell types. The elongation of astrocyte processes is mediated by NrCAM, a cell adhesion molecule induced by astrocyte-specific conditional knockout of Ryk after spinal cord injury. Our findings suggest that Ryk is a promising therapeutic target to accelerate wound healing, promote neuronal survival, and enhance functional recovery.